How a book is made - Aliki (New York : Crowell, 1986)
Describes the stages in making a book, starting with the writing of the manuscript and the drawing of the pictures, and explaining all the technical processes leading to printed and bound copies.
Keywords: Books -- Juvenile literature; Book industries and trade -- Juvenile literature; Publishers and publishing -- Juvenile literature; Printing -- Juvenile literature; Books; Book industries and trade; Publishers and publishing; Printing